Combining realist evaluation and transformative evaluation to advance research in palliative care: The case of end of life companionship. (March 2023) - Downey, John; Fornasiero, Mauro; Cooper, Susan; Bassett, Lynn; Doherty, Margaret; Dubeibe Fong, Alejandra; Bradley, Natasha; Cornwall, Jon
Background: Palliative care requires innovative methods to understand what works, for whom, in what circumstances and why. Realist evaluation has become one prominent approach due to its preoccupation with building, and testing, causal theories to explain the influence of contextual factors on outcomes. Undertaking realist evaluation is not without challenges and may amplify issues of underrepresentation, disempower those working in palliative care, and produce results with poor ecological validity. Complementary approaches are needed which mitigate these challenges, whilst producing credible findings that advances knowledge. Purpose: In this article it is outlined how realist evaluation provides a toolkit to advance research to explain, and empirically test, the complex contours of palliative care. Moreover, it is proposed that transformative evaluation can provide a catalyst to engage and empower those within palliative care, create the opportunity for care transformation, and produce more informed and authentic theories. Discussion: Contemporary issues in palliative care pertain to the complexity of palliative care, the insufficiency of experimental designs alone, and the challenges of achieving inclusive research participation. In this article it is argued that theory led, participatory, opportunistic and naturalistic approaches can provide an antidote to the issues in the literature. The combination also mitigates many methodological critiques of the individual approaches, by increasing the transformative potential of realist evaluation, and explanatory potential of transformative evaluation.